STUDI KASUS TERJEMAHAN TRANSTOOL BAHASA INDONESIA DARI BAHASA INGGRIS - Busyro (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
The objectives of this research are (1) to know the Indonesian transtool translation of English phrases and (2) to know the Indonesian transtool translation of English clauses.This research uses a descriptive-qualitative method, that deccribes the translation of English phrases and clauses into Indonesian. The research data are noun phrases that consist of two and three words, verb phrases that consist of two and three words, adjective phrases that consist of two words, and clauses. The data collection technique used are hearing and taking-note technique.The results of the research show that structurally English and Indonesian noun phrases are different. The structure of English noun phrases consists of modifier and head. Meanwhilw, in Indonesian the head is on the left side. The structures of English and Indonesian verbal phrases that consist of two and three words are the same. The structures of English and Indonesian adjective phrases are the same.Generally, the translation of noun, verb, and adjective phrases using transtool has been good. But, there are still errors. The errors of the transtool translation are on the translation of words, not structures.